Intense visible photoluminescence in Ba(Zr0.25Ti0.75)O-3 thin films - Cavalcante, L. S.; Gurgel, M. F. C.; Simoes, A. Z.; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; Joya, M. R.; Pizani, P. S. (American Institute of Physics (AIP), 2007)
Photoluminescence at room temperature in Ba(Zr0.25Ti0.75)O-3 thin films was explained by the degree of structural order-disorder. Ultraviolet-visible absorption spectroscopy, photoluminescence, and first principles quantum mechanical measurements were performed. The film annealed at 400 degrees C for 4 h presents intense visible photoluminescence behavior at room temperature. The increase of temperature and annealing time creates [ZrO6]-[TiO6] clusters in the lattice leading to the trapping of electrons and holes. Thus, [ZrO5]-[TiO6]/[ZrO6]-[TiO6] clusters were the main reason for the photoluminescence behavior.